Does monetary policy affect bank risk-taking? - Yener Altunbas; Leonardo Gambacorta; David Marqués-Ibá\~nez (European Central Bank (ECB), 2010)
This paper investigates the relationship between short-term interest rates and bank risk. Using a unique database that includes quarterly balance sheet information for listed banks operating in the European Union and the United States in the last decade, we find evidence that unusually low interest rates over an extended period of time contributed to an increase in banks' risk. This result holds for a wide range of measures of risk, as well as macroeconomic and institutional controls.
Keywords: E44; E55; G21; 330; bank risk; credit crisis; monetary policy; Geldpolitik; Kreditgeschäft; Geldpolitische Transmission; Bankrisiko; EU-Staaten